Privacy management practices on facebook factors affecting disclosure of private information and use of privacy settings - Sherry Essam Hanna; Hebatallah Elsemary (Cairo : Sherry Essam Hanna, 2021)
The purpose of this study was to investigate, through descriptive research, the current privacy management practices of Facebook users. Specifically, this study sought to explore factors that may help explain behaviors of disclosing private information on Facebook and using on-site privacy controls as well as providing understanding of each factor{u2019}s contribution to explaining both behaviors. Factors tested in this study were drawn from the communication privacy management theory as well as online-privacy-related literature.487 participants of active Facebook users were purposively chosen to answer an online questionnaire developed to collect the empirical data of this study.Bivariate correlations were first used to examine the relations between independent and dependent variables. Multiple Regression Modeling Analysis was then conducted to identify the factors leading to the aforementioned behaviors.Two-sample t-test as well as one-way analysis of variance (ANOVA) were also used to determine whether a statistically significant difference existed between the means of all factors.Findings suggested the potential of Facebook use rate, motives, perceived control, awareness, trust in Facebook users, prior invasion, protective settings use, gender, and education as a framework to explain privacy management practices of Facebook users. Moreover, gender differences were identified in terms of motives, perceived risks for disclosure, and trust in Facebook as well as other users. It has also been shown that belonging to a certain age group made a significant difference to Facebook use rate, perceived benefits and risks for disclosure, perceived control over shared information, awareness, and trust in both Facebook and other users. Finally, education was found to play a role in the rate of Facebook usage, perceived benefits for disclosure, and having experienced a prior invasion
Thesis (M.Sc.) - Cairo University - Faculty of Mass Communication - Department of Radio and Television
Issued also as CD
Keywords: Communication privacy management theory; Disclosure; Online privacy